2019
DOI: 10.1021/acsami.9b04938
|View full text |Cite
|
Sign up to set email alerts
|

AIE Supramolecular Assembly with FRET Effect for Visualizing Drug Delivery

Abstract: Here, we constructed a nanostructured pH/redox dual-responsive supramolecular drug carrier with both aggregation-induced emission (AIE) and Forster resonance energy transfer (FRET) effects, which enabled selective drug release and monitoring drug delivery and release processes. Taking the hyperbranched polyamide amine (H-PAMAM) with intrinsic AIE effects as the core, poly­(ethylene glycol) (PEG) was bridged on its periphery by dithiodipropionic acid. Then, through the host–guest interaction of PEG and α-cyclod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 45 publications
2
54
0
Order By: Relevance
“…15,16 C5-PTZCN, C5-PTZDCA, and ANTDCA are the compounds that were newly synthesized. Their structures were veried by FT-IR, LCMS (Liquid Chromatography Mass Spectrometry)/HRMS (High-Resolution Mass Spectrometry), and 1 H and 13 C NMR data (see ESI; pages (3)(4)(5)(6) and Fig. (S11-S16) †). PTZ, ANT, ANTA, and BSA were procured from Alfa-Aesar and Sigma Aldrich.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 C5-PTZCN, C5-PTZDCA, and ANTDCA are the compounds that were newly synthesized. Their structures were veried by FT-IR, LCMS (Liquid Chromatography Mass Spectrometry)/HRMS (High-Resolution Mass Spectrometry), and 1 H and 13 C NMR data (see ESI; pages (3)(4)(5)(6) and Fig. (S11-S16) †). PTZ, ANT, ANTA, and BSA were procured from Alfa-Aesar and Sigma Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…3 Since the discovery of the FRET, researchers have been actively utilizing this potential non-radiative tool to unveil numerous facts related to the eld of supramolecular materials and biomedical research and development. 4,5 There is a rapid growth in the invention of donor-acceptor combinations for the FRET applications. However, constructing an appropriate donor-acceptor pair for the FRET is still a challenge because it needs to meet primary inuencing criteria such as distance, spectral overlap, and dipole orientation between donors and acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…AIE-active supramolecular nanomaterials for drug/gene delivery and bioimaging have been fabricated, with which the drug delivery process can be monitored and the therapeutic functions can be regulated upon the external stimuli. [150] Besides, theranostic prodrugs and hybrid materials based on the hostguest interactions of CDs and AIEgens can realize the multifunctional and synergistic therapies with the guidance of FLI, which can satisfied the different clinical demands. [151,152] Recently, Ding et al reported the supramolecular AIE nanomaterials based on the host-guest interaction of α-CDs and PEG, which exhibited high performance for imaging-guided orthotopic pancreatic cancer therapy.…”
Section: Macrocycle-guided Assembly Via Host-guest Interactionmentioning
confidence: 99%
“…Wang et al reported a pH-and redox-responsive supramolecular drug nanocarrier with both AIE and FRET effects. [96] DOX-loaded nanocarriers can be constructed by hyperbranched polyamide amine (H-PAMAM), PEG, and α-CD via hostguest interaction. The strong fluorescence of hyperbranched core H-PAMAM enabled the supramolecular nanocarrier to monitor the dynamic drug release process.…”
Section: Cyclodexrinmentioning
confidence: 99%